2020
DOI: 10.1088/2515-7620/abb831
|View full text |Cite
|
Sign up to set email alerts
|

Using longitudinal survey and sensor data to understand the social and ecological determinants of clean fuels use and discontinuance in rural Ghana

Abstract: Efforts to reduce the health and ecological burdens of household biomass combustion are underway in Ghana, principally by promoting clean cookstoves and fuels. Recent studies have focused on the sustained use of clean cookstoves, but sometimes household adopt a new cookstove and then end use of that stove. In this study, we introduce a novel framework for understanding and encouraging household transitions to cleaner cooking: clean fuel discontinuance. We leveraged data from the Ghana Randomized Air Pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…It has long been observed that receiving or purchasing a new cookstove (adoption) does not mean recipients will sustain use of the stove over time [ 11 – 13 ], which we have also observed in Ghana [ 9 , 10 , 14 ]. Research has found that there are many determinants of cookstove adoption and sustained use, broadly categorized into: (1) household/community characteristics, (2) access issues, and (3) knowledge, perceptions, and attitudes [ 12 , 15 18 ].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has long been observed that receiving or purchasing a new cookstove (adoption) does not mean recipients will sustain use of the stove over time [ 11 – 13 ], which we have also observed in Ghana [ 9 , 10 , 14 ]. Research has found that there are many determinants of cookstove adoption and sustained use, broadly categorized into: (1) household/community characteristics, (2) access issues, and (3) knowledge, perceptions, and attitudes [ 12 , 15 18 ].…”
Section: Introductionsupporting
confidence: 53%
“…Energy access research underscores the importance of the “last mile” (or, more realistically in rural Ghana, last 30 km) of LPG delivery/accessibility [ 14 ]. Few studies have tested how much these logistical barriers impact user demand [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…A limitation of GRAPHS is that there was not comprehensive stove use monitoring during all personal air pollution monitoring sessions or throughout the longer study period. Use of non-intervention stoves was reported during GRAPHS based on weekly household surveys, as reported in the Supporting Information and published elsewhere 63 . However, given the lack of complete stove use monitoring we are unable to undertake a full analysis of the contributions of stove use to observed personal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Another major bottleneck to pellet production and use is the lack of public awareness [ 120 ]. While most Ghanaians still lack clean fuel awareness, others perceive it to be costly [ 138 ]. In Indonesia, the lack of public education has caused biomass pellets to not become common in rural communities [ 139 ].…”
Section: Resultsmentioning
confidence: 99%